The Low-Carbon Economy: A Study of Distributive, Procedural and Corrective Justice - Ulya, Husna Ni’matul; Ridwan, Mohammad; Nur Mahmudah, Siti (El-Barka Journal of Islamic Economics and Business, 2024)
Rapid economic development has significantly impacted the environment, particularly through carbon emissions, threatening human survival. Indonesia, a major global emitter, aims to achieve net-zero carbon emissions by 2060 through a low-carbon economy plan. Justice, a key Islamic principle, is essential in this transition to ensure both worldly and spiritual welfare. This study analyzes the integration of distributive, procedural, and corrective justice in Indonesia's low-carbon economy policies. Using a qualitative critical approach and literature review of policy documents, academic studies, and government reports, the study identifies the role of justice in low-carbon development. Findings reveal that distributive justice demands equitable access to renewable energy resources and subsidies for low-income households. Procedural justice underscores the need for transparency and public participation, as seen in the inclusive formulation of Indonesia's Enhanced Nationally Determined Contributions (ENDC). Corrective justice involves compensatory measures, including job retraining for coal industry workers and ecosystem restoration in deforested areas. The study concludes that achieving justice in a low-carbon economy requires equitable benefit distribution and the prevention of marginalization. Transparent, participatory policies are crucial to address socio-economic impacts while promoting sustainable development. This approach aligns with Islamic values, advocating for balance between individual and societal welfare in transitioning to a low-carbon economy.